Norsminde: A “Køkkenmødding” with Late Mesolithic and Early Neolithic Occupation - H., Søren (Journal of Danish Archaeology, 1989)
Norsminde: A “Køkkenmødding” with Late Mesolithic and Early Neolithic Occupation